Effects of Combined Application of Cow Manure And Inorganic Nitrogen Fertilizer on Growth, Yield and Nitrogen Uptake of Black Rice - Marwanto, Marwanto; Nasiroh, Nasiroh; Mucitro, Bambang G.; Handajaningsih, Merakati (Akta Agrosia, 2018)
The beneficial effects of manure on soil properties, growth, and crop productivity have promoted its use for replacing the application of N fertilizer. However, it is not well understood to what extent N fertilizer was able to be substituted by cow manure. Accordingly, this pot experiment aimed to compare the effect of inorganic N fertilizer application alone with that of the combined use of inorganic N fertilizer with cow manure based on the same amount of total N on growth parameters, yield attributes, and nitrogen (N) uptake of black rice. The experiment was conducted under a screen house condition in Agriculture Faculty, Bengkulu University located at 15 meters altitude above sea level during the summer season of 2015. There were six treatments viz. T1 = 100% N from urea + 0% N from cow manure (0.52 g N + 0.00 g cow manure) pot-1, T2 = 80% N from urea  + 20% N from cow manure  (0.42 g N + 9.55 g cow manure) pot-1, T3 = 60% N from urea + 40% N from cow manure (0.31 g N  + 19.10 g cow manure) pot-1, T4 = 40% N from urea + 60% N from cow manure (0.21 g N + 28.65 g cow manure) pot-1, T5 = 20% N from urea + 80% N from cow manure (0.10 g N+ 38.20 g cow manure) pot-1, and T6 = 0% N from urea + 100% N from cow manure (0.00 g N  + 47.75 g cow manure) pot-1. The amount of inorganic N fertilizer in the form of urea and cow manure applied was calculated based on the recommended rate of 115.00 kg ha-1 for N fertilizer and 10.50 ton ha-1 for cow manure. These treatments were arranged in a Completely Randomized Design and repeated three times. The results showed that the treatments significantly (P ?0.005) affected growth parameters as measured by plant height, the number of leaves, fresh shoot weight, fresh root weight, dry shoot weight, dry root weight, yield attributes as determined by the total number of tillers, the total number productive tillers, grain yield per pot, and N uptake. The highest values for all these variables were obtained in the treatment receiving recommended rate of urea only (100% N from urea + 0% N from cow manure as equivalence) and the lowest in the treatment receiving a100% N from cow manure (0% N from urea + 100% N from cow manure). However, combined treatments of cow manure and inorganic N fertilizer such as 80% N from urea  + 20% N from cow manure, 60% N from urea + 40% N from cow manure 40% N from urea + 60% N from cow manure showed a parity statistically with the treatment receiving 100% N from urea only in maintaining the values for all these variables. Overall, the combined use of inorganic N fertilizer (urea) and cow manure as an equivalence promoted growth and yield of black rice by improving N uptake. Keywords: integrated nutrient management, soil chemical property, Nitrogen uptake, combined fertilizer application, black rice